If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(8+4x)=-10-6x
We move all terms to the left:
-4(8+4x)-(-10-6x)=0
We add all the numbers together, and all the variables
-4(4x+8)-(-6x-10)=0
We multiply parentheses
-16x-(-6x-10)-32=0
We get rid of parentheses
-16x+6x+10-32=0
We add all the numbers together, and all the variables
-10x-22=0
We move all terms containing x to the left, all other terms to the right
-10x=22
x=22/-10
x=-2+1/5
| -46x+23=46x-23 | | 2a(5-4)=a*5-0 | | 2(x=1+x+4) | | 3x+15=–45 | | 2x+12=5x-36 | | 2n-50=1950 | | 3y-2y=-3 | | 2x+(1-x)7=3.5*1 | | 2(x-5)5+7=x+8 | | 5(x-4)=5(x+1)-3 | | 3(a-2)+4a=22 | | ((x*3)+(x*6))/4=9 | | 8x-2=-9+7x | | 6*(y-5)=2*(10+3*y) | | 6*(y-5)=2*(10+3y) | | 2x+0=8x+21 | | 7(z-1)-2(z-5)-z=-5 | | −8x+2=−8x+3 | | 24=-5w+3(w+6) | | 7*x+5*(x-1)=-5+12*x | | 9w-3(2w+2)=15 | | -4-9(-8+2n)=-(2n+12) | | 3(8x+14)=2(13x+14) | | 3x^2+134x-4489=0 | | 1624=x+51*26 | | -45-10n=2(6-10n)-7 | | 5y+3=-2y+24 | | 180=3x+4+11+12x | | 5y+3=-2y=24 | | 6/3x=6 | | 8-4t-3(t-5)=2 | | x-5/7=62/3 |